2021
DOI: 10.1080/17445647.2020.1866702
|View full text |Cite
|
Sign up to set email alerts
|

Flood-induced ground effects and flood-water dynamics for hydro-geomorphic hazard assessment: the 21–22 October 2019 extreme flood along the lower Orba River (Alessandria, NW Italy)

Abstract: The knowledge of flood-induced ground effects and flood-water dynamics is a crucial issue for hydro-geomorphic hazards assessment and mapping, and thus for river management and land use planning. This paper and the related 1:15,000 map illustrate the lower Orba River (NW Italy) and its adjacent floodplain geomorphic response to the 21-22 October 2019 extreme flood. This was estimated to be a 500-years flood and caused severe damage to cultivated fields, structures, and infrastructures. The research is based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…Alluvial quaternary deposits occupy the bottom of the valley. Several small creeks cross the study area with S-N directions that, in the 2019 event, caused flash floods (Mandarino et al, 2021). The geomorphology of the area is characterized by the presence of a hilly landscape with a more steep slope in the Serravalle Formation, in the northern sector.…”
Section: Study Areasmentioning
confidence: 99%
See 2 more Smart Citations
“…Alluvial quaternary deposits occupy the bottom of the valley. Several small creeks cross the study area with S-N directions that, in the 2019 event, caused flash floods (Mandarino et al, 2021). The geomorphology of the area is characterized by the presence of a hilly landscape with a more steep slope in the Serravalle Formation, in the northern sector.…”
Section: Study Areasmentioning
confidence: 99%
“…Several villages and the small town of Gavi are located inside the AOI, henceforth called Gavi area. The Castle of Gavi hill was particularly hit by shallow landslides, as also occurred in 2014, 1977and 1935events (Govi, 1978Mandarino et al, 2021). Historical information tells us that the Liguria region and NW Alps have been affected by several extreme rainfall events, usually during autumn (D'Amato Avanzi et al, 2015;Cevasco et al, 2014;Ferrari et al, 2021;Roccati et al, 2018;Guzzetti et al, 2004;Luino, 1999).…”
Section: Study Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of applications have already been exploited in, e.g., archaeological studies [41,42], management of heritage assets and infrastructure [43][44][45], cataloguing of agricultural spaces [46], and environmental issues [47,48]. Examples of their use in studies on natural risks, such as landslides [49,50], earthquakes [51] and floods [52,53], were presented in the literature as well.…”
Section: Proposal Of a Collaborative Collection Of Training Samples W...mentioning
confidence: 99%
“…Several studies have identified their main causes to be severe human pressures, both at the basin and channel scale, namely in-channel sediment quarrying [4,[19][20][21][22], dam closure [19,[23][24][25][26], channelization [27][28][29], and land use changes [30][31][32]. These interventions, associated with a general economic growth, caused river systems to experience landform simplification, and thus the loss of habitats [9,14,15,33,34], geomorphological instability and related damage to in-channel structures [14,19,33,[35][36][37], as well as floodable area reduction and progressive occupation of the areas of fluvial pertinence [14,27,38]. As a result, serious issues in terms of environmental quality, biodiversity conservation, and hydrogeomorphic hazards and risks arose.…”
Section: Introductionmentioning
confidence: 99%